Hidden Unemployment is Resulting from ineffective Recruitment and Selection Process in Public Sector in KRG (Public banks as a case study) - Kamaran Kamal Kareem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Human Resource Department is a significant part in any origination; it deals with issues related to employees which effects directly performance of origination. It is obvious that effective Recruitment and Selection of employee affect the performance index of the institution. This research answer questions related to employee recruitment and selection process. Through discussing the hidden unemployment whether increases or decreases unemployment rate. In the analytical aspect, the public banks within Erbil city, Iraqi Kurdistan region has been taken as case study.